1991
DOI: 10.1136/adc.66.7.879
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous or intramuscular insulin injections.

Abstract: To find out whether diabetic children may inject their insulin intramuscularly rather than subcutaneously, a random sample of 32 patients aged 4-3-17*9 (median 11.3) years was studied. Distance from skin to muscle fascia was measured by ultrasonography at standard injection sites on the outer arm, anterior and lateral thigh, abdomen, buttock, and calf. Distances were greater in girls (n= 15) than in boys (n= 17). Whereas in most boys the distances were less than the length of the needle (12-5 mm) at all sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 12 publications
3
23
1
Order By: Relevance
“…Similar to our results, Hofman et al showed no gender differences in the subcutis prior to puberty [2], but pubertal girls had thicker subcutis than boys [1], [2], [7]. Our findings also confirm the existing evidence that adult men have thinner subcutis and thicker dermis than women [8][17].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our results, Hofman et al showed no gender differences in the subcutis prior to puberty [2], but pubertal girls had thicker subcutis than boys [1], [2], [7]. Our findings also confirm the existing evidence that adult men have thinner subcutis and thicker dermis than women [8][17].…”
Section: Discussionsupporting
confidence: 92%
“…In 1991, when needles with a length of 12.7 mm were commonly used, Smith et al [11] used ultrasound to measure the distance from the skin to the muscle fascia in 32 boys and girls. These researchers found that the subcutaneous layers were much thinner than anticipated and concluded that ‘most boys and some girls who use the perpendicular injection technique may often inject insulin into muscle, and perhaps on occasions into the peritoneal cavity’.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm earlier observations in diabetic and non-diabetic children. 6,16 At all measuring sites except medially on the buttock, several children had a distance from cutis to the muscle fascia less than the length of the shortest needle (8 mm). Compression of the skin (such as often occurs during an injection) radically reduced the thickness of cutis/subcutis, and even more children had a distance from cutis to muscle fascia of less than 8 mm under these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…4 Great variations in cutis/subcutis thickness at insulin injection sites have been demonstrated in adults 5 and in one study in children. 6 As many children are lean, and as they use insulin injection needles of the same length Sponsors: Novo Nordisk A/S, Denmark * Correspondence to: Dr Niels Birkebaek, Skovgårdsparken 44, DK-7080 Børkop, Denmark as adults (8,12 or 16 mm), they might be at risk of accidental, inappropriate, intramuscular insulin injection even when injecting at a 45°angle to the skin. Indeed, in a recent study of insulin injection in children, 30.5 % of children using a 12 or 16 mm needle were found to have injected intramuscularly.…”
Section: Introductionmentioning
confidence: 99%